(untitled) (Revista Internacional de Formação de Professores, 2019)
As a contribution to think and deepen the possibilities of doing an active pedagogy in Higher Education, I present the report of three experiences that I had the opportunity to perform with my students in undergraduate and post-graduate studies using techniques developed by Freinet and Freire. These experiences allowed the students of Pedagogy to put into practice a little of what they had been learning since the beginning of their course, especially in Didactic classes, about these two educators. Also, the students of the specialization course in Teaching in Higher Education, in the contact with these techniques, came into contact with ideas and practices different from those with which they usually became familiar during the course of their formation.